Silly Sara : a phonics reader - Hays, Anna Jane.; Wickstrom, Sylvie (New York : Random House, 2002)
Alliterative rhyming tale of a girl who can be very silly but with her best friend, Sam, discovers she can be something more.
D., unk, c2000
Preschool-grade 1.
Keywords: Clumsiness -- Fiction; Best friends -- Fiction; Stories in rhyme